Entrepreneurial performance, Innovation platform, Integrated marketing communication and Customer value affect Toward purchasing decisions of restaurant franchising in Thailand - Manmai, Chattip; Kortana, Tanapol; Pungnirund, Bundit; Saisama, Chompoo (วารสารการวิจัยการบริหารการพัฒนา, 2025)
Currently, there are only a few successful Thai restaurant franchises due to a lack of knowledge about franchise systems. A thorough understanding of how to build a proper franchise system is essential to manage a franchise successfully. This research sets out to explore several key objectives. First, it examines the levels of entrepreneurial performance, innovation platforms, integrated marketing communication, customer value, and the purchasing decisions associated with restaurant franchises in Thailand. Secondly, it investigates the influence of these variables on the decision to purchase a restaurant franchise. Lastly, it aims to develop a decision-making model for prospective franchise buyers in the Thai restaurant industry. The study employs a mixed-method approach, incorporating both quantitative and qualitative research. The quantitative aspect focuses on a sample of restaurant franchise entrepreneurs in Thailand, with the sample size determined by a criterion of 20 times the number of observed variables. Multi-stage random sampling was used to select participants, and data collection was carried out through questionnaires. The gathered data was then analyzed using structural equation modeling. In the qualitative phase, in-depth interviews were conducted with 20 key informants, all of whom are Thai restaurant franchise entrepreneurs. The findings revealed that entrepreneurial performance variables, innovation platforms, integrated marketing communication, customer value, and purchasing decisions were rated highly overall. However, integrated marketing communication was noted to be at a moderate level. Furthermore, entrepreneurial performance variables, innovation platforms, integrated marketing communication, and customer value significantly influence purchasing a restaurant franchise, with statistical significance at the 0.05 level. Based on these results, a decision-making model called the "Thai Franchise Restaurant EIIC Model" (E = Entrepreneurial Performance, I = Innovation Platform, I = Integrated Marketing Communication, C = Customer Value) was developed to guide prospective buyers. Additionally, qualitative insights emphasized the importance of creating franchise systems that adhere to international standards. Business owners must also integrate modern management innovations, particularly within the context of the digital era, and utilize advanced information technology to promote their franchise systems effectively. This will enhance decision-making processes for purchasing restaurant franchises in Thailand and ensure future success in this growing market. Theoretically, this study contributes to franchise and consumer decision-making theories by positioning customer value as both an independent and mediating variable in the EIIC model, providing a novel conceptual framework for analyzing purchase behaviors in the Thai franchise context.